S119 MicroRNA-200b represses TGF- β1 induced EMT in BEAS-2B and primary bronchial epithelial cells. (12th November 2015) - Ladak, S; Ward, C; Ali, S
Abstract : Introduction: MicroRNAs (miRNAs) are small non-coding RNAs that function as endogenous gene regulators. They may initiate a process called epithelial-mesenchymal transition (EMT) that leads to aberrant extracellular matrix remodelling and is implicated in a number of airway diseases. Dysregulation of miRNAs has been indicated in chronic lung disorders, the third most common cause of mortality in adults. Materials and methods: NanoString was used to assay the differential expression of miRNAs at 1, 4 and 24 hrs following TGF-β1 treatment of BEAS-2B cells (immortalised primary bronchial epithelial cells) and control. QRT-PCR validated the expression profile of miR-200b. BEAS-2B and PBECs (primary bronchial epithelial cells) were transfected with miR-200b mimics to study expression of EMT markers at mRNA and protein level. MiRNA targets were identified and validated using multiple computational tools and qRT-PCR respectively. Results: nCounter assay allowed identification of novel miRNAs including miR-200 family. MiR-200b mimic transfection (24 hrs) followed by TGF-β1 treatment (48 hrs) demonstrated a significant increase in E-Cadherin (p ≤ 0.05, p ≤ 0.001) and a significant decrease in Fibronectin (p ≤ 0.001, p ≤ 0.01) in BEAS-2B cells and PBECs. Protein studies suggested a similar trend in both the cells. The most prominent targets of miR-200b identified were RHOA, SMURF2, ZNF532 and ZEB2. A significant decrease was observed in ZNF532 (p ≤ 0.01) and ZEB2 (p ≤ 0.001) in miR-200b transfected and TGF-β1 treated BEAS-2B cells (n = 3). Differential expression of mRNA targets was observed in two sets of patient derived PBECs. Conclusion: miR-200b suppressed TGF-β1 induced EMT by maintaining the epithelial framework of BEAS-2B cells and PBECs. Results provide new insights into miR-200b regulation in fibrosis and basis for therapeutic application in lung injury.